2019
DOI: 10.20517/2574-1209.2019.05
|View full text |Cite
|
Sign up to set email alerts
|

Total arterial coronary grafting: outcomes, concerns and controversies

Abstract: Choice of conduit remains the Achilles heel of coronary artery bypass grafting. Conduit choice is crucial as it is deemed to influence the long-term outcomes. While the important survival advantage of a left internal mammary artery graft over vein grafts is universally accepted, controversy reigns supreme regarding the next best conduit. There is plenty of evidence to suggest that arterial grafts are not only superior in terms of patency and survival, but they also protect the native coronary arteries against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
1
2
0
2
Order By: Relevance
“…For the other 12 surgeons, the BIMA use was only 14.45% (0–25%). This variability is consistent with 20% TAG utilization in Europe, up to 80% in some Australian centers ( 39 ) and 3% overall BIMA usage on multi-institutional analysis ( 40 ). A further subgroup analysis is planned as an extension to this study to investigate the effect of surgeon experience on engagement with information provided by the computational modeling.…”
Section: Discussionsupporting
confidence: 77%
“…For the other 12 surgeons, the BIMA use was only 14.45% (0–25%). This variability is consistent with 20% TAG utilization in Europe, up to 80% in some Australian centers ( 39 ) and 3% overall BIMA usage on multi-institutional analysis ( 40 ). A further subgroup analysis is planned as an extension to this study to investigate the effect of surgeon experience on engagement with information provided by the computational modeling.…”
Section: Discussionsupporting
confidence: 77%
“…7 Total arterial revascularization became an alternate option to saphenous vein grafts to improve the long-term outcomes after CABG; however, the superiority of this approach is still debated. 8 Total arterial revascularization has the potential advantage of a better patency rate, lower myocardial infarctions and reoperations, and a better survival rate. 9 This study compared total arterial revascularization strategy and conventional CABG with long saphenous vein grafts.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in the pursuit of TAR, there still needs to further compelling data from RCT to support TAR's use in standard practice 58 . It is also suggested that to achieve TAR, higher levels of surgical dexterity is needed, requiring more intensive training and experience before being able to successfully achieve TAR 9 .…”
Section: Discussionmentioning
confidence: 99%